Visualization of spin-polarized electronic states by imaging-type spin-resolved photoemission microscopy - Koichiro Yaji; Shunsuke Tsuda (Science and Technology of Advanced Materials: Methods, 2024)
Harnessing electron spin is crucial in developing energy-saving and high-speed devices for the next generation. In this scheme, visualizing spin-polarized electronic states aids in designing and developing new materials and devices. Spin-resolved photoemission spectroscopy provides information on the spin-polarized electronic states. To investigate the spin-polarized electronic states in microscopic materials and devices, spin-resolved photoemission spectroscopy requires spatial resolution in a sub-micrometer scale. Here we show the imaging-type spin-resolved photoemission microscopy (iSPEM) with an ultraviolet laser developed at the National Institutes for Materials Science (NIMS). Our iSPEM achieves a spatial resolution of 420 nm, drastically improving by more than an order of magnitude compared to conventional spin-resolved photoemission spectroscopy instruments. Besides, the multichannel spin detector significantly reduces the data acquisition time by four orders of magnitude compared to the conventional instruments. The iSPEM machine elucidates the spin-polarized electronic states of sub-micrometer scale materials, polycrystals, device structure samples, and so on, which have yet to be the target of conventional spin-resolved photoemission spectroscopy.